2020
DOI: 10.1007/s00018-020-03677-7
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic pathways activated by pro-inflammatory cytokines promote mutant p53 stability: clue for novel anticancer therapies

Abstract: Inflammation and cancerogenesis are strongly interconnected processes, not only because inflammation promotes DNA instability, but also because both processes are driven by pathways such as NF-kB, STAT3, mTOR and MAPKs. Interestingly, these pathways regulate the release of pro-inflammatory cytokines such as IL-6, TNF-α and IL-1β that in turn control their activation and play a crucial role in shaping immune response. The transcription factor p53 is the major tumor suppressor that is often mutated in cancer, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 88 publications
1
26
0
Order By: Relevance
“…Interestingly, the overexpression of mutp53 in U87 (Figure 2E), a glioblastoma cell line carrying wtp53, slightly affected cell survival ( Figure 2F) and did not increase intracellular ROS ( Figure 2G,H). As ROS are strongly inter-connected with the release of pro-inflammatory cytokines and other molecules involved in pro-tumorigenic effects induced by mutp53 [10], we then evaluated inflammatory cytokine release by ASPC1 and U87 cells transfected with p53-R273H or with empty vector (EV). Interestingly, multi-analyte Luminex assay analysis indicated that mutp53 increased the release of pro-inflammatory/immune suppressive cytokines by ASPC1 cells and, once again, this effect was not observed in U87 cells ( Figure 2I).…”
Section: Mutp53-r273h Overexpression Increases Cell Survival Ros Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the overexpression of mutp53 in U87 (Figure 2E), a glioblastoma cell line carrying wtp53, slightly affected cell survival ( Figure 2F) and did not increase intracellular ROS ( Figure 2G,H). As ROS are strongly inter-connected with the release of pro-inflammatory cytokines and other molecules involved in pro-tumorigenic effects induced by mutp53 [10], we then evaluated inflammatory cytokine release by ASPC1 and U87 cells transfected with p53-R273H or with empty vector (EV). Interestingly, multi-analyte Luminex assay analysis indicated that mutp53 increased the release of pro-inflammatory/immune suppressive cytokines by ASPC1 cells and, once again, this effect was not observed in U87 cells ( Figure 2I).…”
Section: Mutp53-r273h Overexpression Increases Cell Survival Ros Andmentioning
confidence: 99%
“…Biomolecules 2021, 11, 344 2 of 14 and interleukin 10 (IL-10) [8,9]. Promoting the release of pro-inflammatory cytokines is another oncogenic trait of mutp53 that creates an inflammatory/immune suppressive milieu which strongly promotes tumorigenesis [10]. Interestingly, it is known that most of the effects induced by mutp53 proteins are opposite to those mediated by wild type p53 (wtp53).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms may underlie the stabilization of mutant p53 in cancer cells, including: the presence of tumor-specific stress signals that might normally function to stabilize WT p53, the inability of most mutant p53 proteins to induce the transcription of MDM2, and the ability of mutant p53 proteins to complex with members of the heat shock protein family, induced by the unfolded protein response often active in tumors, which stabilize mutant p53 proteins by preventing interaction with MDM2 ( Wawrzynow et al 2018;Mantovani et al 2019). Furthermore, by disrupting the autophagic machinery in the cell, mutant p53 protects itself from degradation, adding to its stability (D'Orazi et al 2020). Taken together, it appears that, in most cases, mutant p53 has only a partial ability to limit WT p53 function and that this may only become relevant in certain tissues or in response to stress such as DNA damage (Gencel-Augusto and Lozano 2020).…”
Section: Mutant P53mentioning
confidence: 99%
“…p53 is an essential tumor suppressor, and targeting p53 mutation should also be concerned ( D'Orazi et al, 2021 ). Presently, the MP-MB probe has been developed to detect p53 gene.…”
Section: The Application Of Nucleic Acid Probe–based Fluorescent Sensing In Cancer Diagnosis and Treatmentmentioning
confidence: 99%